The effects of secondary stressors, social identity, and social support on perceived stress and resilience: Findings from the COVID-19 pandemic - Ntontis Evangelos; Blackburn Angélique M; Han Hyemin; Stöckli Sabrina; Milfont Taciano L; Tuominen Jarno; Griffin Siobhán M; Ikizer Gözde; Jeftic Alma; Chrona Stavroula; Nasheedha Aishath; Liutsko Liudmila; et al. (Elsevier, 2025)
Primary stressors are direct outcomes of extreme events (e.g., viruses, floodwater) whereas secondary stressors stem from pre-disaster life circumstances and societal arrangements (e.g., illness, problematic pre-disaster policies) or from inefficient responses to the extreme event. Secondary stressors can cause significant long-term damage to people affected but are also tractable and amenable to change. In this study we explored the association between secondary stressors, social identity processes, social support, and perceived stress and resilience. Pre-registered analyses of data from the COVIDiSTRESS Global Survey Round II (N = 14,600; 43 countries) show that secondary stressors are positively associated with perceived stress and negatively associated with resilience, even when controlling for the effects of primary stressors. Being a woman or having lower socioeconomic status (SES) is associated with higher exposure to secondary stressors, higher perceived stress, and lower resilience. Importantly, social identification is positively associated with expected support and with increased resilience and lower perceived stress. However, neither gender, SES, or social identification moderated the relationship between secondary stressors and perceived stress and resilience. In conclusion, systemic reforms and the availability of social support are paramount to reducing the effects of secondary stressors.